2018
DOI: 10.1111/hojo.12267
|View full text |Cite
|
Sign up to set email alerts
|

Critical Reflections on Attention Deficit Hyperactivity Disorder (ADHD) in the Criminal Justice System: Swedish Female Ex‐Offenders’ Narratives of Diagnosis

Abstract: Recent years have seen an emerging link between attention deficit hyperactivity disorder (ADHD) and criminal behaviour. Sweden is a leader in this field of research, and high levels of ADHD are reported in the Swedish criminal justice system. The aetiology of the condition, however, remains unclear and there is definite ambivalence in the literature regarding both diagnosis and treatments. Offering a unique qualitative perspective on the role of ADHD diagnoses, this article critically explores female first‐han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Feminist criminologists have shown the extent to which gender matters in the lives of women with experiences of criminalization and substance abuse, not least in relation to the high exposure to violence and sexual victimization ( 34 ). Desistance research centering the lived experience of female offenders has further revealed how lingering consequences of prior victimization from violence may restrict women’s routes out of crime ( 35 , 36 ). Gender blindness thus risks obscuring the various ways in which structural inequalities affect women’s lived experiences of criminalization and substance abuse, as well as their processes of desistance.…”
Section: Peer Support and Desistance: A Feminist Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Feminist criminologists have shown the extent to which gender matters in the lives of women with experiences of criminalization and substance abuse, not least in relation to the high exposure to violence and sexual victimization ( 34 ). Desistance research centering the lived experience of female offenders has further revealed how lingering consequences of prior victimization from violence may restrict women’s routes out of crime ( 35 , 36 ). Gender blindness thus risks obscuring the various ways in which structural inequalities affect women’s lived experiences of criminalization and substance abuse, as well as their processes of desistance.…”
Section: Peer Support and Desistance: A Feminist Approachmentioning
confidence: 99%
“…These women’s drug use is often seen as causing the violence ( 67 ). Women who engage in criminal behavior or who use drugs risk being treated as doubly deviant for breaking the law as well as the conventional norms of femininity ( 36 , 68 , 69 ).…”
Section: #Metoo and Women With Experiences Of Criminalization And Sub...mentioning
confidence: 99%